Management of patients with colorectal liver metastasis in eleven questions and answers. Issue 12 (1st December 2016) - Andres, Axel; Majno, Pietro; Terraz, Sylvain; Morel, Philippe; Roth, Arnaud; Rubbia-Brandt, Laura; Schiffer, Eduardo; Ris, Frederic; Toso, Christian
ABSTRACT: Introduction: Colorectal liver metastasis (CRLM) is the most frequent indication for liver resection in many centers. Recent improvements in oncology, surgery, interventional radiology, pathology and anesthesiology allow curative treatment in a larger proportion of patients with CRLM. Areas covered: We illustrate the various aspects of the management of CRLM through 11 questions that summarize the topic, from the current obtained survival to future perspectives such as transplantation. The limits of a curative treatment are also presented from different angles, such as the benefits of pathology, the surgical options for extreme resections, the available chemotherapies and their efficacy, or the non-surgical ablative treatments. Expert commentary: Given the increasing therapeutic possibilities, we strengthen the importance to analyze the situation of each patient with CRLM in a dedicated multidisciplinary team, in order to offer the best individualized treatment combination.